Insight into the effect of the vasopressin analog desmopressin on lung colonization by mammary carcinoma cells in BALB/c mice - Garona, Juan (2014)
Background/Aim: Desmopressin (dDAVP) is a synthetic peptide analog of vasopressin with antidiuretic and hemostatic properties. Recent experimental evidence suggested that dDAVP can inhibit metastasis formation by agonist action on V2 vasopressin receptors present in both tumor and endothelial cells. We have examined the kinetics of dDAVP effect during metastatic colonization and its potential association with hemostasis. Materials and Methods: The experimental metastasis assay was performed by injecting F3II mammary carcinoma cells into the lateral tail vein of syngeneic female BALB/c mice. Results: Clinically relevant doses of dDAVP (0.3 to 2 μg/kg intravenously (i.v.)) produced a dose-dependent inhibition in the formation of lung nodules when administered during the first 24 hours after F3II tumor cell injection. The hemostatic agent tranexamic acid (10 mg/kg, i.v.) had not effect on metastasis formation in the same experimental conditions, while the anticoagulant enoxaparin (1 mg/kg, subcutaneously (s.c.)) did not modify the antimetastatic action of dDAVP. In vitro, dDAVP had a strong inhibitory effect on F3II cell colony formation. Conclusion: dDAVP interferes with early metastatic disease, and direct association of this effect with hemostatic mechanisms is unlikely.